Evaluation of response to treatment of mixed trypanosome infection in goats using the polymerase chain reaction - Burudi, E.M.E.; Peregrine, A.S.; Majiwa, Phelix A.O.; Murphy, N.B. (OAU/STRC, 1995)
Studies on infections with drug-resistant trypanosomes indicate that the majority of parasites in a population are sensitive to the drug dose used to select the population (Mamman et al., 1993). This study was initiated to examine whether a drug-resistant trypanosome population could influence the survival of a drug-sensitive population in mixed infections in goats. To identify both populations during the course of a mixed infection, a system for distinguishing between them was required. Arbitrary primer Polymerase Chain Reaction (PCR) was attempted, but was unable to distinguish the two populations if one was 10 percent or less of the total number of parasites. Using a DNA sequence that is only present in the diminazene-sensitive trypanosome, T. congolense IL 1180, a pair of 20 bp primers were designed, which, in a PCR, amplified a 900 bp sequence from IL 1180 but not IL 3274. The sensitivity of the PCR technique for detecting Il 1180 genomic DNA, when mixed with 25 ng total genomic DNA of IL 3274 was 100 pg by gel electrophoresis and ethidium bromide staining of the PCR products. Using the 900 bp PCR product as a 32 P-labelled probe in southern blots, the sensitivity was increased 100-fold. Three groups of 5 goats each were infected intravenously with either IL 1180 (group A), IL 3274 (group B) or both clones simultaneously (group C), and treated with diminazene aceturate at a does of 7.0 mg/kg b.wt following Development of parasitaemia. Animals in group C were treated after all animals in groups A and B had become parasitaemic. There other groups (groups D, E and F), consisting of 3 goats each, were similarly infected and kept as untreated controls. All group A animal sgot cured, while all in B and 4 in C relapsed. Trypanosomes were harvested from all animals every 2 weeks, beginning 3 days before treatment and up to 60 days post-treatment. Trypanosome DNA was analysed for the presence of IL 1180 DNA was absent in any post-treatment sample. It was therefore concluded that IL 1180 is unable to survive treatment with diminazene aceturate when mixed with IL 3274.